Demonstrating social attitudes and tourism – reflections on the multi-aspect nature of connections - Sójka, Dagmara (Turystyka – to znaczy co? Uroboros czy Feniks, 2025)
The aim of this paper is to present the issue of demonstrating social attitudes in the context of tourism. The author shares her research observations on the interrelationship of the two issues. This text does not represent a typical analysis of research results, but is devoted to subjective reflections on the areas where demonstrating is combined with tourism and where they influence each other. The paper does not constitute an in-depth analysis of the themes identified but provides directions for further inquiry. The formulation of this text was inspired by Ludwig Wittgenstein’s approach, which avoids quotations and focuses on presenting his own individual reflections (Wittgenstein, 2012). This way of considering the subject matter discussed, given the specific framing of the problem, is, in the author’s opinion, the most accurate.